2022
DOI: 10.1371/journal.pone.0279333
|View full text |Cite
|
Sign up to set email alerts
|

One-year cardiovascular outcomes after coronavirus disease 2019: The cardiovascular COVID-19 registry

Abstract: Background The long-term cardiovascular (CV) outcomes of COVID-19 have not been fully explored. Methods This was an international, multicenter, retrospective cohort study conducted between February and December 2020. Consecutive patients ≥18 years who underwent a real-time reverse transcriptase-polymerase chain reaction (RT-PCR) for SARS-CoV2 were included. Patients were classified into two cohorts depending on the nasopharyngeal swab result and clinical status: confirmed COVID-19 (positive RT-PCR) and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
0
21
1
Order By: Relevance
“…Several studies have reported that COVID-19 infected patients have a higher incidence of cardiovascular events, including acute myocardial infarction, stroke, and heart failure, within one year of infection [ 31 ]. Additionally, Katsoularis et al conducted a self-controlled case series and matched cohort study in Sweden, which showed an increased risk of acute myocardial infarction and ischemic stroke following COVID-19 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that COVID-19 infected patients have a higher incidence of cardiovascular events, including acute myocardial infarction, stroke, and heart failure, within one year of infection [ 31 ]. Additionally, Katsoularis et al conducted a self-controlled case series and matched cohort study in Sweden, which showed an increased risk of acute myocardial infarction and ischemic stroke following COVID-19 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…195,197,198 A large retrospective study of 153 760 COVID-19 survivors found that when compared with controls without the infection, the risk of cardiovascular events (including ischemic heart disease, heart failure, inflammatory heart disease, arrhythmias, cerebrovascular events, thromboembolic events, and other cardiac disorders) remains increased by 63% at 1 year even after adjustment for traditional cardiovascular risk factors and pre-COVID-19 health care utilization. 195 Subsequent studies have confirmed the elevated risk of cardiovascular events [197][198][199] and subsequent risk of mortality. 200,201 The proposed mechanisms linking COVID-19 infection with an increased risk of cardiovascular events are similar to those described from other bacterial and viral infections.…”
Section: Covid-19mentioning
confidence: 94%
“…In the same year, Ortega-Paz et al published the results of an international, multicenter cohort study with 4,427 participants (3,578 in the COVID-19 and 849 in the control cohort, respectively) who were followed up for incident venous thrombosis between 31 and 365 days after the acute phase (in the COVID-19 cohort). 12 After 1 year of follow-up, patients who recovered from COVID-19 had an almost 10fold higher risk of developing venous thrombotic episodes (adjusted HR, 9.33; 95%CI, 2.93-29.70). Older age, male sex, length of hospital or ICU stay, and mechanical ventilation were found to be significant predictors of adverse cardiovascular events.…”
Section: Postcoronavirus Disease Venous Thrombosismentioning
confidence: 95%